PERANCANGAN GAME EDUKASI BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN MATA PELAJARAN DASAR DESAIN GRAFIS UNTUK KELAS X (Studi Kasus pada SMK As-Saabiq) - Tika Restina; Sulidar Fitri; Taofik Muhammad (PRODUKTIF : Jurnal Ilmiah Pendidikan Teknologi Informasi, 2023)
This study aims to design learning media in the form of games. This study uses research and development methods (Research and Development). In the stages of this research process there are analysis, design, development, implementation and testing stages. The tests carried out were in the form of validations carried out by media experts and material experts. Then the media is tried out by students, after validation and the media meets the appropriate interactive criteria, then testing or research is carried out to determine feasibility in the field. This research was conducted at SMK As Shaabiq Singaparna involving 31 students. Data collection techniques in this study used a questionnaire, then the data obtained was analyzed. In this study, the feasibility results of material experts, media experts and students were obtained with an average score. Thus it can be concluded that the game can be used as a proper learning media. This research has the following results: (1) Producing an educational game using Construct 2 as a learning medium for Basic Graphic Design (2) This educational game has a Decent quality in the balance testing aspect with an eligibility percentage of 76.39%, Decent quality in the playtesting aspect with an eligibility percentage of 80 .16%, and proper quality in the usability testing aspect with a feasibility percentage of 78.06%. From the total results it can be concluded that this educational game is categorized as feasible with a feasibility percentage of 78.2%. Keywords : Learning media, Educational games, Questionnaires.